In Vivo Evaluation of 68Ga-Labeled NOTA-EGFRvIII Aptamer in EGFRvIII-Positive Glioblastoma Xenografted Model - Jun Young Park; Ye Lim Cho; Tae Sup Lee; Daekyun Lee; Ju-Hyung Kang; Soryong Lim; Yujin Lee; Jae Hyun Lim; Won Jun Kang (Pharmaceutics, 2024)
EGFRvIII is expressed only in tumor cells and strongly in glioblastoma and is considered a promising target in cancer diagnosis and therapy. Aptamers are synthetic single-stranded oligonucleotides that bind to biochemical target molecules with high binding affinity and specificity. This study examined the potential of the 68Ga-NOTA-EGFRvIII aptamer as a nuclear imaging probe for visualizing EGFRvIII-expressing glioblastoma by positron emission tomography (PET). EGFRvIII aptamer was selected using the SELEX technology, and flow cytometry and fluorescence microscopy verified the high binding affinity to EGFRvIII positive U87MG vIII 4.12 glioma cells but not to EGFRvIII negative U87MG cells. The EGFRvIII aptamer was conjugated with a chelator (1,4,7-triazanonane-1,4,7-triyl)triacetic acid (NOTA) for 68Ga-labeling. The 68Ga-NOTA-EGFRvIII aptamer was prepared using the preconcentration-based labeling method with a high radiolabeling yield at room temperature. Ex vivo biodistribution analyses confirmed the significantly higher tumor uptake of the 68Ga-NOTA-EGFRvIII aptamer in EGFRvIII-expressing xenograft tumors than that in EGFRvIII negative tumors, confirming the specific tumor uptake of the 68Ga-NOTA-EGFRvIII aptamer in vivo. PET imaging studies revealed a high retention rate of the 68Ga-NOTA-EGFRvIII aptamer in U87MG vIII 4.12 tumors but only low uptake levels in U87-MG tumors, suggesting that the 68Ga-NOTA-EGFRvIII aptamer may be used as a PET imaging agent for EGFRvIII-expressing glioblastoma.